Crystallization and optical properties of Nd3+ doped ferroelectric glass-ceramics in the barium sodium niobosilicate system. (July 2015) - Boonsong, P.; Tipakontitikul, R.; Monmaturapoj, N.; Niyompan, A.
Abstract: Ferroelectric glass-ceramics of the Na2 O–BaO–Nb2 O5 –SiO2 system were obtained from a controlled crystallization process performed on the parent glass of composition 20Na2 O–10BaO–30Nb2 O5 –40SiO2 . Nd2 O3 doping content was varied in the range 0, 0.1 and 0.5 mol%. Thermal properties of the as-quenched sample were studied by DTA technique and the results of DTA showed a possible crystallization peak at 740 °C and this was selected as the treatment temperature. The obtained glass-ceramics were investigated in terms of crystalline phase formation by XRD technique, microstructure by SEM and optical property using UV–visible spectroscopy. Fluorescence spectra of the glass-ceramics were also recorded at RT. The results of XRD revealed that NaNbO3 and Ba2 NaNb5 O15 were the dominant crystalline phases. The microstructures of the glass-ceramics reveal randomly distributions of small crystallites with the size in the range 0.17–0.19 µm. At low Nd 3+ content, the glass-ceramics were transparent material. With a yellow light excitation at 580 nm, the glass-ceramic shows possible emissions in the ultraviolet, blue and green light region.